Rapid, Noninvasive Diagnosis of Balamuthia mandrillaris Encephalitis by a Plasma-Based Next-Generation Sequencing Test. (1st June 2020) - Kalyatanda, Gautam; Rand, Kenneth; Lindner, Martin S; Hong, David K; Sait Albayram, Mehmet; Gregory, Jason; Kresak, Jesse; Ibne, Karim M Ali; Cope, Jennifer R; Roy, Shantanu; Gary, Joy M; Reddy, Varalakshmi; et al.
Abstract: Granulomatous amoebic encephalitis (GAE) caused by Balamuthia mandrillaris is a rare subacute infection with exceptionally high mortality. Diagnosis is typically made by brain biopsy or at autopsy. Detection of Balamuthia mandrillaris cell-free DNA by next-generation sequencing of plasma enabled rapid, noninvasive diagnosis in a case of amoebic encephalitis.